Impaired Glucose Metabolism Is Associated with Visit-to-Visit Blood Pressure Variability in Participants without Cardiovascular Disease - Nobuo Sasaki; Ryoji Ozono; Saeko Fujiwara; Ryo Maeda; Yasuki Kihara (International Journal of Hypertension)
We evaluated data from 10,088 participants without cardiovascular disease (CVD) who underwent 75 g oral glucose tolerance tests and had more than four visits during the first 5 years following the test to investigate the association between impaired glucose metabolism and visit-to-visit blood pressure (BP) variability. Participants were classified into groups of normal glucose tolerance (NGT), impaired fasting glucose (IFG), impaired glucose tolerance (IGT), and diabetes. Visit-to-visit BP variability was estimated for each individual using standard deviation (SD) and coefficients of variation (CV, defined as SD/mean). SDs and CVs of systolic BP (SBP) values were divided into quartiles. The samples falling in the highest quartile were considered as having high SD/CV. The adjusted odds ratio (OR) for high SD of SBP in the IFG (OR, 1.39; P<0.003), IGT (OR, 1.26; P<0.001), and diabetes (OR, 1.54; P<0.001) groups was significantly higher than that for high SD of SBP in the NGT group. Similarly, the OR for high CV of SBP in the IGT and diabetes groups was significantly higher than that for high CV of SBP in the NGT group. In participants without CVD, impaired glucose metabolism may modulate visit-to-visit BP variability.